Environmental geotechnics in practice : introduction and case studies - Sarsby, R. W. (ICE Publishing, 2019)
Environmental Geotechnics in Practice is an informative and practical guide to the realities of land-based waste disposal. Drawing together significant case histories from across the world where key lessons have been learned, the book provides an engaging overview of this important field. Focusing on land-based waste disposal sites where there is significant interaction between ground engineering and the environment, coverage includes key elements of a wide variety of waste disposal systems, environmental threats posed, and ways that environmental damage can be prevented. Together, the case histories demonstrate that whatever type of waste is being disposed of it is possible to use geotechnical principles and practices to design a suitable facility.